Obstacles and facilitators to preventing fetal alcohol spectrum disorder: a qualitative study with general practitioners - Leruste, Sébastien; Baelen, François; Doray, Bérénice; Maillard, Thierry; Marimoutou, Catherine; Spodenkiewicz, Michel (Frontiers in Medicine, 2024)
Background: Fetal Alcohol Spectrum Disorders are the leading cause of non-genetic intellectual disability. The damage caused, although completely preventable, is irreversible and requires lifelong support. General Practitioners have an important role in the prevention of Fetal Alcohol Spectrum Disorders. However, evidence suggests that General Practitioners don't monitor systematically alcohol consumption among pregnant women.Objectives: The aim of this study was to understand the barriers and motivations of General Practitioners in the prevention of Fetal Alcohol Spectrum Disorders on Reunion Island. Methods: A qualitative research study was conducted by conducting semi-structured individual interviews with general practitioners. Participants were selected by random or snowball sampling. General practitioners who worked only in unscheduled care services were excluded from this study. After the interviews were transcribed, a verbatim analysis was performed according to the principles of grounded theory.Results: Twenty interviews were conducted by two researchers between November and December 2020. General practitioners expressed discomfort in addressing alcohol consumption and excessive drinking in women. They had inaccurate theoretical knowledge and a lack of practical experience with Fetal Alcohol Spectrum Disorders. They also showed little knowledge of the Fetal Alcohol Spectrum Disorders care pathway available on Reunion Island. Both patients and general practitioners expressed discomfort when discussing women's alcohol consumption. Conflicting government policies were highlighted as alcohol promotion campaigns overshadowed Fetal Alcohol Spectrum Disorders prevention initiatives.Conclusion: General practitioners should be open and non-judgmental in their interactions with women and couples, with a focus on early detection and short-term intervention. General practitioners should be better educated about Fetal Alcohol Spectrum Disorders and have a clearer understanding of the Fetal Alcohol Spectrum Disorders care pathway.